Optimizing Iron Ore Matching for Sintering Based on High Temperature Characteristic Numbers - Zhao, Yong; Wu, Keng; Zhan, Wen-long; Zhu, Chun-en; Du, Xiao-dong (9th International Symposium on High-Temperature Metallurgical Processing, 2018)
In view of the traditional evaluation index of sintering basic characteristics ignoring process information, several high temperature characteristic numbers, which contain process information, were used to evaluate the sintering basic characteristics more comprehensively in this paper. The evaluation model of iron ore properties was established based on the high temperature characteristic numbers with employing fuzzy mathematics. Then, with the constraint of sinter properties and the raw materials, the ore blending model was built, whose target was to obtain the lowest cost and the best sinter properties. A multi-objective fuzzy linear programming was used to solve the model in order to get the best ore matching schemes. The ore blending model was then applied to the practical production, which was proved to be dependable.